Leadership and Governance Practices: Influencing Quality Education in Ethiopian Private Higher Education - Chali, Gudata Abara (The Indonesian Institute of Science and Technology Research, 2026)
The rapid expansion of private higher education institutions (PHEIs) in Ethiopia has significantly increased access to tertiary education; however, concerns regarding educational quality remain substantial. This article critically examines the relationship between leadership, governance, and educational quality within Ethiopian PHEIs by integrating contemporary theories of educational leadership with the national regulatory framework, including Proclamation No. 1152/2019 and HERQA guidelines. The study adopts a conceptual and analytical approach to explore how leadership effectiveness and governance practices influence institutional quality outcomes. The analysis emphasizes key dimensions such as strategic resource management, faculty professional development, curriculum relevance, innovation, accountability, transparency, and stakeholder participation. The article further proposes a multivariate analytical framework capable of examining the interdependent relationships between leadership indicators, governance structures, and multiple dimensions of educational quality. Particular attention is given to contextual challenges facing Ethiopian PHEIs, including regulatory compliance, institutional capacity limitations, and tensions between financial sustainability and academic excellence. The findings suggest that ethically grounded, strategically aligned, and context-responsive leadership supported by transparent governance systems is essential for sustaining educational quality and institutional credibility. The article concludes by providing practical recommendations for policymakers, institutional leaders, and accrediting agencies to strengthen governance mechanisms and leadership capacity in Ethiopian PHEIs. This study contributes academically by connecting global leadership theories with Ethiopian higher education realities while offering a framework for future empirical investigation and policy reform.